Accumulating Evidence of the Impact of Voter ID Laws: Student Engagement in the Political Process. Issue 1 (1st January 2018) - McConville, Kelly S.; Stokes, Lynne; Gray, Mary
ABSTRACT: Recently, voter ID laws have been instituted, modified, or overturned in many states in the U.S. As these laws change, it is important to have accurate measures of their impact. We present the data collection methods and results of class projects that attempted to quantify the impact of the voter ID laws in areas of three states. We also summarize the types of data used to assess the impact of voter ID laws and discuss how our data address some of the shortcomings of the usual techniques for assessing the impact of voter ID laws.